Sir D. B. Jayatilaka : a biography and assessment of the man and his work - Wijesekera, Nandadeva, 1909- (Dept. of Cultural Affairs, Govt. of Sri Lanka, 1973)
Biography of Sir Don Baron Jayatilaka, 1868-1944, Ceylonese statesman and scholar.